(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2016)
The great technical inventions as a result from the scientific investigation that was processed in since the XIX century until our days and the use of new energy sources made humanity pass through successive industrial revolutions giving rise to the so-called modern society. This article intends to analyze the role of man and new technologies in actual society.